Supporting Procedural and Perceptual Learning in Laparoscopic Surgery. (September 2014) - Lou, Y.; Flinn, J. T.; Ganapathy, S.; Weyhrauch, P.; Niehaus, J.; Myers, B.; Cao, C. G. L.
Expertise in surgical performance requires mastery of both technical skills such as suturing, and nontechnical skills such as perceptual and procedural knowledge. "Refresher-training" after skill decay due to nonuse should consider the fact that non-technical skills often decay faster than technical skills. To support the re-learning of perceptual and procedural knowledge, this study examined the effectiveness of different design factors for digital training material. The factors considered included modality/fidelity of representation (illustration/cartoon vs. realistic/video images) and task difficulty (easy, medium, and difficult). Results suggest that low fidelity images are better for perceptual learning, and are equally effective as high fidelity images for procedural learning. The level of difficulty of the procedures did not affect performance in this study of novices, but may be an important factor with more experienced trainees. Time and error results indicate that refresher training in perceptual and procedural knowledge should begin with a procedural task to review surgical steps, followed by a perceptual task, to achieve greater efficiency and effectiveness.